OxInflammation: From Subclinical Condition to Pathological Biomarker - Valacchi, Giuseppe; Virgili, Fabio; Cervellati, Carlo; Pecorelli, Alessandra (Frontiers in Physiology, 2018)
Inflammation is a complex systemic response evolved to cope with cellular injury, either due to infectious agents or, in general, with sporadic events challenging tissue integrity and function. Researchers involved in different fields have the tendency to look at the inflammatory response with different angles, according to their specific interest. Established its complexity, one of the most evident features of the inflammatory response is the generation of a pro-oxidative environment due to the production of high fluxes of pro-oxidant species. This production starts locally, at the site of injury or infection, but eventually becomes a chronic challenge for the organism, if the inflammatory response is not properly controlled. In this review, we focus on this specific aspect of chronic, low-level sub-clinical inflammatory response. We propose the term “OxInflammation” as a novel operative term describing a permanent pro-oxidative feature that interact, in a positive feed-back manner, to a not yet clinically detectable inflammatory process, leading in a long run (chronically) to a systemic/local damage, as a consequence of the cross talk between inflammatory and oxidative stress mediators. Therefore, it could be useful to analyse inflammatory markers in pathologies where there is an alteration of the redox homeostasis although an inflammatory status is not clinically evident.